Mapping of the PhDs in the private sector: A literature review - Susanna Stén (The Research Institute of the Finnish Economy (ETLA), 2008)
This review maps out the labour market situation of PhDs employed in the private sector. To begin with, the theoretical motives for employing PhDs and the supporting empirical evidence are examined. The potential benefits of companies from employing PhDs can be divided into productivity and innovation effects as well as knowledge contributions from networking, and external effects. Next, the international empirical literature on PhDs in the private sector is surveyed. The mostly US based research focuses primarily on PhDs in the fields of science and engineering. It provides no synoptic picture of the employment situation of the PhDs in the private sector and leaves a need for further research. A more detailed review of the Finnish literature shows that the private sector employs only about 15% of all PhDs in the Finnish labour market. There is, however, large variation between different fields of study, genders and age groups. The rapid increase in graduating PhDs in recent years indicate that the employment patterns of PhDs might be changing. Further research is needed to answer questions like: How has the increased supply changed the labour market situation of PhDs? Has the role of the private sector as an employer of PhDs changed? And is the allocation of PhDs between fields of study efficient? Another issue that has earned only very little attention is the mobility of PhDs in the labour market. Mobility within and between sectors is very important for both the diffusion of knowledge in the economy and the development of the career and wage profiles of PhDs. Because of the recent development, the existing knowledge gaps and the rapidly ageing research conducted up to this day, there is, thus, an urgent need for further research in this field.
Keywords: J24; J44; J6; 330; PhDs; private sector; career; wages; employment; Akademische Berufe; Privatwirtschaft; Erwerbsverlauf; Arbeitsmobilität; Gehalt; Finnland; USA